Key pieces of the politically correct thought in the colombian constitutional culture: War and arms versus peace, legalism and legal purism (2018)
In this article, some aspects of traditional political and juridically correct thinking in Colombia are analyzed in a critical perspective. Aspects that tend to overlap and disperse as loose pieces, considered innocuous, of the local constitutional history. Here the communicating vessels are established between the prejudices and topics usually exhibited in university law studies, and in the press, and the commonplaces repeated without shame in essays such as the recent and successful one. Why does Colombia fail? by Enrique Serrano (2016). The ideas that are developed are the following: a) The fallacy of the opposition between Bolívar and Santander, awarding to him the weapons and to this the laws as something more «natural» of the Colombian national being; b) The falsity of the Colombian democratic exemplary because it has not had military dictatorships like other Latin American countries; c) The forgetting of what has been and is the Law, which is so invoked, for the Colombian oligarchy. d) The always problematic Colombian social reality to which the Law can not and should not be alien. © 2018, Corporacion Universitaria Republicana. All rights reserved.